Marketing Mix Analysis In An Effort For Formulating Strategies To Increase The Number Of Students (High School Case Study) - Ari Lestari (Institute of Computer Science (IOCS), 2022)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have spiritual, religious, self-control, personality, intelligence, noble character and skills needed by themselves, society and the nation. The problem faced by the College of Informatics and Logic Management is that the 2017-2021 enrollment target is not achieved. So that if no real action is taken, it is feared that it will have an impact on this High School. This study aims to formulate policies and alternative strategies based on the marketing mix in order to improve the decision to choose a Logic College in the future. The independent variables studied were derived variables from the marketing mix strategy, namely Product, Price, Location, Promotion, People, Process and Service. As for the dependent variable, namely the Decision to Choose.